New Projects in the Field of Cultural Tourism - I. Dashevskaya (Евразийская интеграция: экономика, право, политика, 2019)
The study analyzes the new forms of cultural tourism through a theoretical justification on the examples of special events for painters. It introduces three types of organizing plein air tours (amateur, commercial and social), analyzes the positive and the negative components of each type, and suggests a holistic approach as a perfect model of a plein air tour.